Cyclosporine A up‐regulates Sonic hedgehog in gingiva: role of the up‐regulation on gingival cell proliferation. (14th May 2014) - Chung, Y.; Fu, E.
<x xml:space="preserve">Abstract</x> Background and Objective Sonic hedgehog protein (SHH) is a mitogen that stimulates cell proliferation. Cyclosporine A enhances the proliferation of gingival cells; however, the relationships of SHH to cyclosporine A or to cyclosporine A‐enhanced gingival cell proliferation have not been described. Material and Methods Here, we investigated SHH expression in gingiva in vitro and in vivo after cyclosporine A treatment and tested the effect of SHH inhibition on cyclosporine A‐enhanced gingival fibroblast proliferation in vitro. Results In human gingival fibroblasts, cyclosporine A treatment increased the expression of SHH transcripts and SHH protein, and stimulated cell proliferation; the addition of cyclopamine, an SHH signaling inhibitor, suppressed cyclosporine A‐enhanced cell proliferation. Up‐regulated expression of SHH and up‐regulation of proliferating cell nuclear antigen transcripts and protein were observed in the edentulous gingiva of cyclosporine A‐treated rats. Conclusion Cyclosporine A up‐regulates gingival SHH expression in vitro and in vivo, and the inhibition of the SHH pathway counteracts the stimulatory effect of cyclosporine A on gingival fibroblast proliferation. Therefore, we suggest that SHH mediates a novel molecular mechanism for cyclosporine A‐induced gingival complications.